International Guidelines for Standardization of Sustainable Development of the Administrative and Territorial Entities: Russian Experience of Implementation - BURAK, Petr Iosifovich; ZVORYKINA, Tatiana Ivanovna; IVANOVA, Galina Nikolaevna; IVANOV, Aleksey Dmitrievich; ALADIN, Vitaly Vladimirovich (Journal of Advanced Research in Law and Economics; Vol 6 No 3 (2015): JARLE Volume VI, Issue 3(13), Winter 2015, 2017)
The article considers theoretical and practical aspects of the formation of activities in the area of standardization of sustainable development of the administrative and territorial entities. This innovative area of standardization provides the formalization of indicators and performance factors of such universally recognized elements of sustainable development as support for the environment, economic development and implementation of social policy. Standardization in this case is focused on the development of international, interstate and national standards regulating the methodology of the system approach to the formation of indicators to assess the performance of the the administrative and territorial entities, as well as forms and methods of managing performance quality of executive and municipal authorities. Currently, an international technical committee ISO/TC 268 ‘Sustainable Development in Communities’ is formed at the international level. The main purpose of the committee was the development of international standards in the field of sustainable development of the administrative and territorial entities. The mirror committee TC 115 ‘Sustainable Development of the administrative and territorial entities’ is set up in the Russian Federation. The objectives of the committee include adaptation and harmonization of international standards to Russian conditions. The problems involved the establishment of sound indicators and factors that characterize the sustainable development in the regions of Russia, require serious scientific study and preparation of a set of actions for use in Russia. The created standards will establish indicators and factors that characterize the sustainable development of regions of the Russian Federation.